Draft genome sequence of Methylobacterium sp. strain V23, isolated from accretion ice of the Antarctic subglacial Lake Vostok - Sapp, Amanda; Huguet-Tapia, José C.; Sanchez Lamas, Maximiliano; Antelo, Giuliano Tomás; Primo, Emiliano David; Rinaldi, Jimena Julieta; Klinke, Sebastian; Goldbaum, Fernando Alberto; Bonomi, Hernán Ruy; Christner, Brent C.; Oteroc, Lisandro H. (Genome Announcements)
Here, we report the draft genome sequence of Methylobacterium sp. strain V23, a bacterium isolated from accretion ice of the subglacial Lake Vostok (3,592 meters below the surface). This genome makes possible the study of ancient and psychrophilic genes and proteins from a subglacial environment isolated from the surface for at least 15 million years. Fil: Sapp, Amanda. University of Florida; Estados Unidos Fil: Huguet-Tapia, José C. University of Florida; Estados Unidos Fil: Sanchez Lamas, Maximiliano. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Investigaciones Bioquímicas de Buenos Aires. Fundación Instituto Leloir. Instituto de Investigaciones Bioquímicas de Buenos Aires; Argentina Fil: Antelo, Giuliano Tomás. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Investigaciones Bioquímicas de Buenos Aires. Fundación Instituto Leloir. Instituto de Investigaciones Bioquímicas de Buenos Aires; Argentina Fil: Primo, Emiliano David. Universidad Nacional de Río Cuarto. Facultad de Ciencias Exactas Fisicoquímicas y Naturales. Departamento de Biología Molecular; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Rinaldi, Jimena Julieta. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Investigaciones Bioquímicas de Buenos Aires. Fundación Instituto Leloir. Instituto de Investigaciones Bioquímicas de Buenos Aires; Argentina Fil: Klinke, Sebastian. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Investigaciones Bioquímicas de Buenos Aires. Fundación Instituto Leloir. Instituto de Investigaciones Bioquímicas de Buenos Aires; Argentina Fil: Goldbaum, Fernando Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de ...